An annotated check list of the Cicadomorpha and Fulgoromorpha (Hemiptera) of the Madeira and Salvages archipelagos - Aguin-Pombo, Dora; Freitas, Carlos (Zootaxa, 2008)
The volcanic archipelagos of Madeira and Salvages located respectively at 635 km and 373 km offshore of the northeastern African coast are very rich in endemic species. These two archipelagos together with the Canary Ils and the archipelagos of Cape Verde and Azores represent part of the Mediterranean hot spot which is considered the richest area in flora and fauna of Europe. To synthesize the knowledge on these groups, an annotated checklist of Cicadomorpha and Fulgoromorpha of the archipelagos of Salvages and Madeira is presented based on published literature including data on distribution and food plants. In addition 9 new species records are reported: Austragallia caboverdensis, Austragallia sinuata, Balclutha rufofascia, B. hebe, Cicadella viridis, Macrosteles sexnotatus, Recilia angusticeps, Tamaricella cf fasciolata and Zyginidia lineata. The checklist comprises 79 species of 7 different families. Of these species 87% occur in Madeira and 10% in the Salvages archipelago. As a whole 27% are endemic to Madeira and 8% are endemic to Macaronesia. Despite this diversity, knowledge of their habitats and food plants is still very scarce.KEY WORDS: Homoptera, Auchenorrhyncha, distribution, new records, Madeira, Hemiptera, MacaronesiaMacaronesian archipelagos are included in the Mediterranean hot spot which is the richest area in flora and fauna of the European Union (Médail and Quézel, 1999). The Macaronesia subregion located between Eurasia